The effects of schizophrenia on the family: a review and personal account - O'Brien, Angela Sue (Kansas State University, 2008)
Schizophrenia can be an extremely disabling individual disorder but it is also clear that it is a "family disorder" as well. Researchers have begun to assess the correlates and possible causes of this disorder on families in the United States as well as in other nations. This report reviews this research. Most research to date has focused on two aspects of the schizophrenia-family relationship: expressed emotion and sense of burden. Following a definitional review of schizophrenia, its history, and its treatment, this report reviews research conducted on expressed emotion (relative's propensity to express critical, hostile, or over involved attitudes about a patient when discussing the patient's illness with an interviewer) and sense objective and subjective of burden of care provision. A personal account is offered regarding what it was like for the writer to grow up in a family with a parent diagnosed with schizophrenia. Finally, the conclusion of this report evaluates the strengths and weaknesses of current research on the impact of schizophrenia and the family. Suggestions for future research are derived partially from the content of the personal account. These include the need for a research targeting the full family, developmentally- and contextually-appropriate theories to guide the research, and the need for more qualitative research to identify individual and family variables that should guide future empirical efforts. It is suggested that programmatic family education and counseling should begin soon after diagnosis of the disorder, be developmentally relevant, and designed to sustain family members over long periods of time.
Keywords: Schizophrenia and effect on family; Sociology, Individual and Family Studies (0628)